Human‐Induced Pluripotent Stem Cells Generate Light Responsive Retinal Organoids with Variable and Nutrient‐Dependent Efficiency. (13th August 2018) - Hallam, Dean; Hilgen, Gerrit; Dorgau, Birthe; Zhu, Lili; Yu, Min; Bojic, Sanja; Hewitt, Philip; Schmitt, Michael; Uteng, Marianne; Kustermann, Stefan; Steel, David; Nicholds, Mike; et al.
Abstract: The availability of in vitro models of the human retina in which to perform pharmacological and toxicological studies is an urgent and unmet need. An essential step for developing in vitro models of human retina is the ability to generate laminated, physiologically functional, and light‐responsive retinal organoids from renewable and patient specific sources. We investigated five different human‐induced pluripotent stem cell (iPSC) lines and showed a significant variability in their efficiency to generate retinal organoids. Despite this variability, by month 5 of differentiation, all iPSC‐derived retinal organoids were able to generate light responses, albeit immature, comparable to the earliest light responses recorded from the neonatal mouse retina, close to the period of eye opening. All iPSC‐derived retinal organoids exhibited at this time a well‐formed outer nuclear like layer containing photoreceptors with inner segments, connecting cilium, and outer like segments. The differentiation process was highly dependent on seeding cell density and nutrient availability determined by factorial experimental design. We adopted the differentiation protocol to a multiwell plate format, which enhanced generation of retinal organoids with retinal‐pigmented epithelium (RPE) and improved ganglion cell development and the response to physiological stimuli. We tested the response of iPSC‐derived retinal organoids to Moxifloxacin and showed that similarly to in vivo adult mouse retina, the primary affected cell types were photoreceptors. Together our data indicate that light responsive retinal organoids derived from carefully selected and differentiation efficient iPSC lines can be generated at the scale needed for pharmacology and drug screening purposes.Stem Cells 2018;36:1535–1551 Abstract : Five iPSC lines differentiated to light responsive retinal organoids with variable efficiency. Seeding density and nutrient availability had the most dominant effect on retinal organoid formation. Using a high‐throughput compatible multiwell format, we showed that drug testing is compatible with this system.